True faith and allegiance : immigration and American civic nationalism - Pickus, Noah M. Jedidiah, 1964- (Princeton University Press, 2007)
True Faith and Allegiance is a provocative account of nationalism and the politics of turning immigrants into citizens and Americans. Noah Pickus offers an alternative to the wild swings between emotionally fraught positions on immigration and citizenship of the past two decades. Drawing on political theory, history, and law, he argues for a renewed civic nationalism that melds principles and peoplehood. This tradition of civic nationalism held sway at America's founding and in the Progressive Era. Pickus explores how, from James Madison to Teddy Roosevelt, its proponents sought to combine reas.